Durability and strength properties of Triplochiton scleroxylon wood treated with Thevitia peruviana seed oil after fungal attack - Adebawo, F. G. (2022)
The effect of Thevitia peruviana seed oil treatment on weight loss and compressive strength of decayed sap wood of Triplochiton scleroxylon was investigated. The phytochemical analysis of methanolic extracted T. peruviana seed oil was determined qualitatively and quantitatively after which five concentration levels (0, 25, 50, 75 and 100%) were prepared. The treated and untreated (control) samples were inoculated with Pleurotus ostreatus and Fibroporia vaillantii for 14 weeks and their weight loss and maximum compressive strength (MCS//) were determined. Data obtained were analysed using Analysis of Variance at α0.05. The phytochemical analysis showed that saponins, flavonoid, steroid, terpenoids and coumarin were present. Untreated samples gave weight loss of 42.67 and 50.05% for P. ostreatus and F. vaillantii respectively while the lowest weight losses of 15.09 and 13.93% were observed in specimen treated with 100% concentration level of oil for P. ostreatus and F. vaillantii respectively. The maximum compressive strength of 9.25 and 8.93 N mm-² for untreated samples and highest maximum compressive strength of 16.39 and 15.42 N mm-² for treated samples were observed in specimen exposed to P. ostreatus and F. vaillantii, respectively. All results showed that 100% concentration level of oil extract was effective in protecting T. scleroxylon wood against fungal decay.